Manual disaster emergency preparedness for Person with Disabilities (PwDs) in Malaysia - Abdul Rahim, Asiah; Abd Samad, Nur Amirah; W Seman, Wan Mohamad Amin (Global Research and Development Services, 2017)
Emergencies usually occur suddenly and disastrously and it can leave you feeling overwhelmed and powerless. Being prepared can lessen some of these feelings by allowing the public to better protect themselves, families, and property, and to help others who may be affected. From time to time, communities around Malaysia face catastrophic natural disasters that give big impact on the country. Tsunami 26 December 2004 and the flood in Kelantan December 2014, are examples of disasters in recent years that garnered national attention. Emergency can occur suddenly, with little or no warning; deprive families of even the most basic food and shelter; and have significant social and emotional impacts that linger long after the event. This manual will be the guideline of management in facing the future disaster focusing on persons with disabilities (PwDs) those who have long term physical, mental, intellectual or sensory impairments, whom their interaction with various organisations may hinder their full and effective participation in society before, during, and after an emergency. The methodology applied for this paper by using focus group discussion by the experts who have experiencing managing disaster at local authorities, officer from fire department, National Disaster Management Agency (NADMA) and others. Secondary data was gathered from literature review such as journals, articles, books and others. The data will be analysed using combined method qualitative and quantitative. The contribution of this Manual Disaster Preparedness for Person with Disabilities (PwDs) will provide emergency preparedness programs with tools and resources to guide Malaysian on planning process based on emergency preparedness cycle, which includes Pre-emergency,Emergency and Post emergency for the future to assist PwDs in any disasters.